2020
DOI: 10.1101/2020.08.14.248880
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alpha-1-antitrypsin and its variant-dependent role in COVID-19 pathogenesis

Abstract: Entry of SARS-CoV-2 is facilitated by endogenous and exogenous proteases. These proteases proteolytically activate the SARS-CoV-2 spike glycoprotein and are key modulators of virus tropism. We show that SARS-CoV-2 naïve serum exhibits significant inhibition of SARS-CoV-2 entry. We identify alpha-1-antitrypsin (AAT), and to a lesser degree, alpha-2-macroglobulin (A2M) as highly abundant serum protease inhibitors that potently restrict protease-mediated entry of SARS-CoV-2. AAT inhibition of protease-mediated SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 88 publications
2
38
0
1
Order By: Relevance
“…We encourage that these agents are to be administered-as stated above-together with camostat or dutasteride once patients are admitted to the hospital and continued throughout the hospitalization period to provide adequate prophylaxis against COVID-19 respiratory complications particularly ARDS. 46,47,49 We also emphasize here that such antiprote- patients, there are at least six published randomized controlled trials. [111][112][113][114][115][116] Most of the trials are of small sample size and show either no benefit or only a mild reduction in time to symptoms resolution with low certainty.…”
Section: Comb Ination Prote a S E-targ E Ting Ther Apymentioning
confidence: 92%
See 2 more Smart Citations
“…We encourage that these agents are to be administered-as stated above-together with camostat or dutasteride once patients are admitted to the hospital and continued throughout the hospitalization period to provide adequate prophylaxis against COVID-19 respiratory complications particularly ARDS. 46,47,49 We also emphasize here that such antiprote- patients, there are at least six published randomized controlled trials. [111][112][113][114][115][116] Most of the trials are of small sample size and show either no benefit or only a mild reduction in time to symptoms resolution with low certainty.…”
Section: Comb Ination Prote a S E-targ E Ting Ther Apymentioning
confidence: 92%
“…Similar to HNE inhibitors, these properties make AAT a promising candidate for managing COVID-19 patients. 49 Like sivelestat, the toxicity profile of AAT therapy should not limit its use in COVID-19 patients. The most common adverse reactions are typical of intravenous infusion of proteins and include fever, chills, urticaria, nausea, vomiting, and fatigue.…”
Section: Alpha1 Antitrypsin (Aat)mentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning other genetic predisposing factors, of particular interest is a study that experimentally demonstrated that Alpha 1 antitrypsin is an inhibitor of Transmembrane protease serine 2 (TMPRSS2) enzyme in a dose-dependent manner and this may explain the preventive effect of COVID-19 infection naïve plasma for viral entry in model systems [1] , [4] . Indeed, the Structure-based computational predictions of protein-protein interactions (Struct2Net – http://cb.csail.mit.edu/cb/struct2net/webserver ) also showed the probability of interaction to be 0.386 using the 1k9o and 1ezx PDB crystal structures.…”
Section: The Hypothesismentioning
confidence: 99%
“…Importantly, a recent study identified AAT as a novel inhibitor of TMPRSS2, which plays a role in the cellular entry of several coronaviruses, including severe acute respiratory syndrome (SARS)-coronavirus (CoV)-2, SARS-CoV, and Middle East respiratory syndrome-CoV, as well as influenza viruses [37][38][39][40]. AAT impedes SARS-CoV2 cellular entry and prevents the main clinical complications of severe COVID-19, such as acute inflammation and acute respiratory failure [41]. Therefore, it could be hypothesized that the geographical distribution of pathogenic variants of AAT protein is to a certain extent linked to differences in COVID-19 epidemiology and severity throughout Europe [42].…”
Section: Protease Complexed and Cleaved Forms Of Aatmentioning
confidence: 99%